2019
DOI: 10.1186/s13048-019-0542-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a new technique for laparoscopic management of ovarian endometriosis preventing recurrence and keeping ovarian reserve

Abstract: Introduction Laparoscopic cystectomy provides more favourable outcomes as regards the recurrence and subsequent clinical pregnancy rates. It is associated with significant reduction in the ovarian reserve due to the inevitable removal of unaffected ovarian tissue. The aim of our study was to evaluate the efficiency of Surgicel in preventing recurrence of endometriomas after their laparoscopic conservative management (cystectomy or drainage). Material and methods A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
(23 reference statements)
1
33
0
1
Order By: Relevance
“…Although it may preserve ovarian reserve, it is not the gold standard for treatment of ovarian endometriomas [16]. Whenever possible, laparoscopic cystectomy should be the first choice, since it can reduce recurrence, raise chance of natural pregnancy and diminish chronic pelvic pain [4,14,23]. Once the cyst wall is tightly adherent to the ovary, complete resection can sometimes be difficult to perform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it may preserve ovarian reserve, it is not the gold standard for treatment of ovarian endometriomas [16]. Whenever possible, laparoscopic cystectomy should be the first choice, since it can reduce recurrence, raise chance of natural pregnancy and diminish chronic pelvic pain [4,14,23]. Once the cyst wall is tightly adherent to the ovary, complete resection can sometimes be difficult to perform.…”
Section: Discussionmentioning
confidence: 99%
“…Once the cyst wall is tightly adherent to the ovary, complete resection can sometimes be difficult to perform. If that is the case, it can either lead to destruction of healthy ovarian tissue; or partial resection can leave endometriotic cells at place, raising the chance of recurrence [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as the presence and growth of endometrial tissue outside of the uterine cavity and often causes chronic pelvic pain, infertility, menstrual disorders, and pelvic masses ( 3 5 ). Endometriosis is a benign disorder but has a high recurrence rate after treatment ( 6 ) and may develop into ovarian endometrioid and clear cell cancer ( 7 , 8 ). Although a number of studies have been carried out to understand the etiology of endometriosis, its detailed pathogenesis remains unclear ( 9 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the recurrence rate of ovarian endometriosis after conservative surgery varies from 6.4% to 43.3% [5,6]. Disease recurrence and repeat surgery increase morbidity and health care costs while significantly damaging ovarian reserve and adversely affecting fertility [7]. Therefore, to prevent the recurrence of ovarian endometriosis after conservative surgical treatment, it is essential to better understand the correlative factors associated with the recurrence of this disease.…”
Section: Introductionmentioning
confidence: 99%